Influence of parenting styles and social adjustment on the psychological well-being of undergraduate working adults in South-West, Nigeria (2019)
The transition of young adults from secondary school to higher institution is not usually easy task. Many undergraduate working adults are confronted with higher academic demands which in one way or the other are beyond their expectations mentally, emotionally, and socially. This has resulted in high level of depression, academic distress and frustration particularly Nigerian university undergraduates. This activated an investigation on the predictive influence of social adjustment and parenting style on psychological well-being of undergraduate working adults in three South-West universities. The correlational research design was adopted for this study. A sample of 218 was drawn from three universities. Data were collected with valid-instruments having suitable reliability coefficient mean value of 0.7. The study revealed that social adjustment and parenting style jointly predicted undergraduate psychological well-being of undergraduate working students. The independent variables accounted for 33.9% variance in students psychological well-being. Social adjustment was found to be the strongest predictor of students' psychological well-being, followed by authoritative, authoritarian and permissive style of parenting. It was inferred that an increase in social adjustment, authoritative parenting style and authoritarian parenting style will increase the tendency for students to display positive psychological well-being. Permissive parenting style will reduce the tendency for students to exhibit negative psychological well-being. It was recommended that parents should adopt authoritative and sometimes authoritarian styles, rather than permissive style of parenting. Parents are enjoyed to expose their children to the reality of life so that they might find it easy to cope outside their homes. Giving assignment of different sorts will also help build their personality and resistance to rigour.